Alternating minimum mean square error hybrid beamforming algorithm in mmWave MIMO system - Min SHEN; Hao XU; Yun HE; Pengguang ZHOU (Dianxin kexue)
The two-stage hybrid beamforming architecture can solve the problem of limited number of RF chains effectively.However,it is still difficult to design a hybrid beamforming algorithm with better performance.In order to achieve higher spectral efficiency,an alternating minimum mean square error (Alt-MMSE) hybrid beamforming algorithm was proposed.Firstly,the initial digital matrix by using the orthogonal properties of the digital matrix was designed,and then the digital matrix by minimizing the square error of the transmitted signal and the received signal was updated.During each iteration,the phase of the analog matrix could be obtained from the updated digital matrix and the optimal fully digital matrix.The simulation results show that the proposed algorithm has better performance and is closer to fully digital beamforming than OMP hybrid beamforming algorithm and hybrid processing scheme based on matrix decomposition .